Healthy Living: Scrambling for a Variety of Foods - Linda B. Bobroff (EDIS)
Unscramble the words to spell some of the foods that are wise choices for good health. Then write down each of the numbered letters on the blanks to figure out the message! This revised 1-page handout was written by Linda B. Bobroff and published by the UF Department of Family Youth and Community Sciences, December 2010.